Assessment of community healthcare providers ability and willingness to respond to emergencies resulting from bioterrorist attacks - Crane Jeffery; McCluskey James; Johnson Giffe; Harbison Raymond (Journal of Emergencies, Trauma and Shock, 2010)
Introduction: Previous findings have demonstrated that preparedness and planning within the public health system are inadequately developed to respond to an act of biological or chemical terrorism. Methods:This investigation used Internet-based surveys to assess the level of preparedness (PL) and willingness to respond (WTR) to a bioterrorism attack, and identify factors that predict PL and WTR among Florida community healthcare providers. Invitations were sent to 22,800 healthcare providers in Florida, which resulted in 2,279 respondents. Results: Respondents included physicians (n=604), nurses (n=1,152), and pharmacists (n=486). The results indicated that only 32% of Florida healthcare providers were competent and willing to respond to a bioterrorism attack, 82.7% of providers were willing to respond in their local community, and 53.6% within the State. Respondents were more competent in administrative skills than clinical knowledge (62.8% vs. 45%). Areas in which respondents had the highest competency were the initiation of treatment and recognition of their clinical and administrative roles. Areas in which respondents showed the lowest competency were the ability to identify cases and the ability to communicate risk to others. About 55% of the subjects had previous bioterrorism training and 31.5% had conducted emergency drills. Gender, race, previous training and drills, perceived threats of bioterrorism attack, perceived benefits of training and drills, and feeling prepared were all predictors of overall preparedness. Conclusions: The findings suggest that only one-third of Florida community healthcare providers were prepared for a bioterrorism attack, which is an insufficient response rate to effectively respond to a bioterrorism incident.